PENERIMAAN ORANG TUA PADA ANAK BERKEBUTUHAN KHUSUS DI DESA TIMPUK KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Marlina, Iis; Zakso, Amrazi; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe goal of the study was to determine parental acceptance of childrenwith special needs by examining the type of parental acceptance, thetreatment given to abk by parents, and the factors that influence parentalacceptance. A qualitative research paradigm was applied, with aphenomenological approach and data collection procedures such asobservation, interview, and documentation. Because of God's supremesacrifice and will, children with exceptional needs were well welcomed bytheir families, according to the findings. There are six types of parentalacceptance in children with exceptional needs. However, the mostimportant of the four is (1) to calm his spirit and accept with sincerity, 2)to provide aid and recognition, which can be observed when parents arenot ashamed or awkward to bring their children, 3) to pay adequateattention, and 4) to have additional patience. There are children who arecomplimented by their parents for receiving good treatment from theirfamilies, such as addressing the needs of children, offering affection in theform of touch, hugs, providing education, or teaching religious science.Children are treated unfairly in the form of mocking, bullying, scolding,lack of support, and being misjudged. Wrong treatment causes subliminalrejection in children with exceptional needs, as others notice parents whoare less loving toward their children. The acceptability of children withspecial needs is inextricably linked to their surroundings. The mostimportant component in determining parental approval is 1) Support fromextended relatives 2) Family unity, 3) Religious background, 4)Community Environment, and 5) Family Economic Situation.Keywords: Parental Acceptance, Special Needs Children